Experimental study on mechanical behaviors of concrete with large-size recycled coarse aggregate. (1st September 2016) - Li, Tan; Xiao, Jianzhuang; Zhu, Cimian; Zhong, Zheng
Highlights: RAC with large-size recycled coarse aggregates was designed, mixed and tested. Different strength indexes and failure pattern of this type RAC were investigated. The relationship of LRCA incorporation rate and cube compressive strength was established. Abstract: In this paper, a new type of recycled aggregate concrete (RAC) with waste concrete as large-size recycled coarse aggregates (LRCA) was designed and prepared. Due to the maximum size of LRCA being 80 mm, the waste concrete crushing process is simplified and therefore has the advantage of high production efficiency. In this paper, strength indexes and failure pattern of this type RAC were experimentally studied. Research parameters included the incorporation rate of LRCA, the maximum size of LRCA, the original strength of waste concrete and the strength of corresponding natural aggregate concrete (NAC). Cube compressive test shows that the difference between cube compressive strength of concrete with LRCA and that of corresponding NAC is small. When the maximum size of LRCA is 80 mm, and the incorporation rate of LRCA reaches 40%, the cube compressive strength is only decreased by 14%. When the incorporation rate of LRCA is lower than 30%, no significant reduction appears in cube compressive strength. The ratio of axial compressive strength to cube compressive strength of RAC with 80 mm maximum size of LRCA is 12% lower than that of corresponding NAC. The difference of splitting tensile strength between this type of RAC and corresponding NAC is lower than 10%. It is also observed that the cracking surface of crushed specimens often passed through the LRCA.